ANALISIS PENGARUH PERTUMBUHAN GDP, TINGKAT SUKU BUNGA, PERTUMBUHAN EKSPOR, PERTUMBUHAN KREDIT DAN BOPO TERHADAP NON PERFORMING LOAN PADA BANK UMUM DI INDONESIA TAHUN 2010 - 2014 - Adicondro, Yesica Yulian; Demi Pangestuti, Irene Rini (Diponegoro Journal of Management, 2015)
This Research aims to analyze the influence of GDP growth, interest rate risk, export growth, credit growth, and operating cost to operating income ratio (BOPO) to credit risk that measured by NPL. Studies on commercial banks in Indonesia during the period 2010 â€“ 2014. The data used in this study are monthly data from January 2010 to December 2014 were taken from various sources. This study uses multiple linear regression analysis. The result shows that the growth of GDP has a negative and significant association with NPL, the interest rate and the ratio of Operating cost to operating income Â positive and significant association with NPL, export growth and no significant negative effect on the NPL. Credit growth and no significant positive effect on the NPL. The results of regression estimation show the ability of model prediction is 40,8% while the remaining 59,2% influenced by other factors outside the model.